Analisis Yuridis Kekuatan Perjanjian Lisensi Merek terhadap Pembatalan Merek dalam Perspektif Kepastian Hukum - Muhammad Anwar Syadat; Diky Dikrurahman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze legal protection for licensees in cancelled trademark license agreements and examine the strength of license agreements for cancelled trademarks from the perspective of legal certainty. The research method used is normative juridical with a legal and conceptual approach. The results of the study indicate that Law Number 20 of 2016 concerning Trademarks and Geographical Indications does not explicitly regulate the position of licensees after trademark cancellation. Legal protection for licensees is obtained through contract law, the principle of good faith and civil liability mechanisms. License agreements cannot be implemented after the trademark cancellation decision has permanent legal force.